2009
DOI: 10.1007/s12144-009-9051-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimism for the World’s Future versus the Personal Future: Application to Environmental Attitudes

Abstract: Optimism and pessimism for the future have been widely studied, but little is known about distinctions among types of optimism. In the present work optimism for the personal future and optimism for a more global world's future were shown to be related yet distinct variables among responses from 156 undergraduate students. Furthermore, World Optimism predicted lower levels of pro-environmental attitudes (the New Ecological Paradigm) whereas Personal Optimism did not after its shared variance with World Optimism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 30 publications
0
7
1
1
Order By: Relevance
“…Contrary to our predictions, personal or collective perceived control did not predict psychological well-being. Past research has shown that perceived control in personal events is related to higher positivity in future thoughts and well-being (Brown, 2012;McElwee & Brittain, 2009). The present studies differ from the previous ones in the type of perceived control measured.…”
Section: Psychological Well-beingcontrasting
confidence: 97%
See 1 more Smart Citation
“…Contrary to our predictions, personal or collective perceived control did not predict psychological well-being. Past research has shown that perceived control in personal events is related to higher positivity in future thoughts and well-being (Brown, 2012;McElwee & Brittain, 2009). The present studies differ from the previous ones in the type of perceived control measured.…”
Section: Psychological Well-beingcontrasting
confidence: 97%
“…However, little is known about how personal and collective future thinking differ in perceived control over the relevant events. Research has suggested that perceived control for future events tends to go hand-in-hand with optimism about the future (McElwee & Brittain, 2009;Topcu & Hirst, 2019. Given that people tend to perceive their personal future to be brighter than their country's future (Shrikanth et al, 2018;Yamashiro & Roediger, 2019), they may view the personal future as more under control than the collective future.…”
Section: Perceived Control For Personal and Collective Eventsmentioning
confidence: 99%
“…For example, with regard to self-guides , as noted earlier, Ouellette and her colleagues (2005) found that those scoring high in CFC were more motivated to exercise after contemplating their ideal future self, whereas those low in CFC were more motivated to exercise after contemplating prototypes of other exercisers (which presumably highlighted normative concerns of what one “should do”). With regard to end goals , research has shown that those scoring high on the CFC-Future subscale are more likely than those scoring low on the CFC-Future subscale to forgo smaller, certain rewards in favor of larger but less certain rewards (Joireman & Balliet, 2012), consistent with the idea that CFC-Future is associated with a tendency to focus on “pursuing (uncertain) gains.” Similarly, research has shown that those scoring high on the CFC-Immediate subscale are more likely to opt for smaller, immediate rewards over larger, delayed rewards (Joireman et al, 2008), consistent with the idea that CFC-Immediate is associated with a tendency to focus on “preventing (immediate) losses.” Finally, with regard to cognitive style s, research has shown that those scoring high in CFC are more optimistic than those scoring low in CFC (O’Brien-McElwee & Brittain, 2009; Strathman et al, 1994), suggesting connections with an “eager” style. On the other hand, high scores on the CFC-Immediate subscale are associated with higher trait hostility (Joireman, Anderson, & Strathman, 2003, data reanalyzed at the subscale level), suggesting connections with a more “vigilant” style.…”
Section: Linking Individual Differences In Cfc With Regulatory Focusmentioning
confidence: 99%
“…Students were more likely to believe positive futures would occur compared to the negative futures [ 24 ]. Similarly, undergraduates were more likely to be optimistic about their personal futures compared to the world’s future [ 25 ]. Optimism has been seen in about 80% of people regardless of race, religion and age [ 18 ].…”
Section: Introductionmentioning
confidence: 99%